Rozhdennye v SSSR: 28 let - Miroshnichenko, Sergey (Russia : Miroshnichenko, Sergey ; Jupp, Jemma, 2012)
Following the idea of Michael Apted, film director Sergey Miroshnichenko documented the lives of the “last Soviet generation” from across the former Soviet Union. Starting when they were seven – just before the collapse of the communist empire – the director returned to the protagonists every seven years to re-examine their lives, decisions, and opinions. Now 28 years old, most of them seem rather disillusioned with the modern Russia in which they find themselves. While some are pining for the old order of their childhood, others are determined to master their own destinies.
Verzio Film Festival Submission
Duration: 01:44:00
Verzio Film Festival Submission
Keywords: Documentary films